Peran Orang Tua Dalam Meningkatkan Kecerdasan Spiritual Anak Usia Dini (Indonesian Journal of Learning Education and Counseling, 2019)
Spiritual intelligence is someone's intelligence in giving meaning. Spiritual intelligence is more important than emotional intelligence and intellectual intelligence. Because spiritual intelligence is a driving force for other intelligences. Therefore, this intelligence must be increased so that it can develop and can be a driving force for other intelligences. To improve spiritual intelligence, it should start as early as possible even since the child is still in the womb, this intelligence has begun to be planted. In this case, of course, the roles and skills of parents determine the process of improving children's spiritual intelligence. Because parents are the first educators for children. This study uses the library research method. The purpose of this study was to find out how the roles and steps of parents in improving children's spiritual intelligence and what factors are supporting in increasing children's spiritual intelligence. The results of this study indicate that in an effort to improve children's spiritual intelligence, parents are the main role. Both his role as an educator, as a role model, as a motivator and as a giver of love. Because in the process there are many obstacles and factors that affect children's spiritual intelligence.